An overview on the mycoparasitic Piptocephalis (Zoopagomycota): taxonomic notes and geographic distribution with new occurrences for South America - da Cruz, Mateus Oliveira [UNESP]; de Freitas, Leslie Waren Silva; Dos Santos, Francisca Robervânia Soares; de Souza-Motta, Cristina Maria; Santiago, André Luiz Cabral Monteiro de Azevedo (FapUNIFESP (SciELO), 2023)
Piptocephalis includes mycoparasitic fungi, mainly targeting mucoralean species. Until now, there has been no compilation of data on the taxonomy and geographic distribution of Piptocephalis, which is a barrier to the proper identification of species of this genus by taxonomists. The present study provides an overview of Piptocephalis with taxonomic and occurrence data, in addition to reporting P. graefenhanii and P. xenophila for the first time in South America. Both species were observed parasitizing Mucor spp. The P. graefenhanii was observed growing on paca dung and P. xenophila was observed on guinea-pig dung in Recife, northeastern Brazil. Aspects of their morphology are discussed and a key for the genus is presented.
Keywords: Ecology; Haustorial fungi; Mycoparasitic fungi; Taxonomy; Zoopagales